Revolutionizing Science Learning: A CRT Based E-Module Integrating Javanese Gamelan to Foster Critical Thinking - Safutri, Safutri; Agnafia, Desi Nuzul; Zahrotin, Anis (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Developing an e-module based on Culturally Responsive Teaching integrated with Javanese gamelan on the material of wave vibrations for grade eight junior high school, to train students’ critical thinking skills and increase the relevance of learning to local culture. Based on the low level of students’ critical thinking skills, it can be seen in the 2022 PISA results with an average score of 383. Methodology: Research and Development with a 4-D development model (define, design, develop, disseminate). The study involved expert validation, limited trials, and field trials on students of Junior high school 6 Ngawi. Data were collected through critical thinking ability tests, student and teacher response questionnaires, and statistical tests using SPSS and Microsoft Excel. Main Findings: The e-module is feasible and effective for training students' critical thinking skills. Independent sample t-test revealed significant differences between the experimental and control groups, with the percentage of the practicality questionnaire reaching 90%, indicating a positive response from students and teachers to the e-module. Novelty/Originality of this study: The uniqueness of this research lies in the integration of physics concepts with local wisdom of Javanese gamelan in an interactive e-module. The Culturally Responsive Teaching model allows learning to be more contextual, interesting, and relevant for students, while contributing to cultural preservation through science education.